Interleukin-6 signaling in patients with chronic heart failure treated with cardiac resynchronization therapy - Katarzyna Ptaszynska-Kopczynska; Anna Szpakowicz; Marta Marcinkiewicz-Siemion; Anna Lisowska; Ewa Waszkiewicz; Marcin Witkowski; Piotr Jakim; Bogdan Galar; Wlodzimierz J. Musial; Karol A. Kamiński (Archives of Medical Science, 2016)
Introduction: Increased expression of interleukin-6 (IL-6) has been described in left ventricular dysfunction in the course of chronic heart failure. Cardiac resynchronization therapy (CRT) is a unique treatment method that may reverse the course of chronic heart failure (CHF) with reduced ejection fraction (HF-REF). We aimed to evaluate the IL-6 system, including soluble IL-6 receptor (sIL-6R) and soluble glycoprotein 130 (sgp130), in HF-REF patients, with particular emphasis on CRT effects. Material and methods: The study enrolled 88 stable HF-REF patients (63.6 ±11.1 years, 12 females, EF < 35%) and 35 comorbidity-matched controls (63.5 ±9.8 years, 7 females). Forty-five HF-REF patients underwent CRT device implantation and were followed up after 6 months. Serum concentrations of IL-6, sIL-6R and sgp130 were determined using ELISA kits. Results : The HF-REF patients had higher IL-6 (median: 2.6, IQR: 1.6–3.8 vs. 2.1, IQR: 1.4–3.1 pg/ml, p = 0.03) and lower sIL-6R concentrations compared to controls (median: 51, IQR: 36–64 vs. 53. IQR 44–76 ng/ml, p = 0.008). There was no significant difference between sgp130 concentrations. In the HF-REF group IL-6 correlated negatively with EF (r = –0.5, p = 0.001) and positively with BNP (r = 0.5, p = 0.008) and CRP concentrations (r = 0.4, p = 0.02). Patients who presented a positive response after CRT showed a smaller change of sIL-6R concentration compared to nonresponders (ΔsIL-6R: –0.2 ±7.1 vs. 7 ±14 ng/ml; p = 0.04). Conclusions : HF-REF patients present higher IL-6 and lower sIL-6R levels. IL-6 concentration reflects their clinical status. CRT-related improvement of patients’ functional status is associated with a smaller change of sIL-6R concentration in time.